Perfil dos acadêmicos de Economia da UFAM e sua identificação com o Curso: uma abordagem qualitativa - Verônica Vieira da Silva (Universidade Federal do Amazonas, 2016)
The aim of this study was to evaluate the profile of the students admitted to the course in Economic Sciences UFAM in the period from 2009 to 2011, noting their identification with the course and with the characteristics presented in pedagogical and political project. It was necessary to analyze the various forms of admission into higher education institutions in the country in order to identify possible difficulties faced by students that helped in some way, the lack of demand for the course. Therefore, studies on the programs of the MEC, in addition to literature review of various authors helped develop this scientific research. The application of questionnaires to assess the profile above among students Economics course of FES and their analysis concludes that research.